(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Moringa oleifera Lam., also known as the ‘drumstick tree,’ is recognized as a vibrant and affordable source of phytochemicals, having potential applications in medicines, functional food preparations, water purification, and biodiesel production. The multiple biological activities including antiproliferation, hepatoprotective, anti-inflammatory, antinociceptive, antiatherosclerotic, oxidative DNA damage protective, antiperoxidative, cardioprotective, as well as folk medicinal uses of M. oleifera (MO) are attributed to the presence of functional bioactive compounds, such as phenolic acids, flavonoids, alkaloids, phytosterols, natural sugars, vitamins, minerals, and organic acids. In these study Different assay of Antioxidant such as DPPH radical scavenging assay, Scavenging activity of Nitric Oxide, Scavenging activity of Superoxide radical, Scavenging activity of Hydroxyl radical, Reducing Power and chelating activity showed highest activity show in methanol extract of leaves as compared to stem bark. In all extract methanol and petroleum ether show highest antioxidant activity.